Skin sympathetic nerve activity in humans during exposure to emotionally-charged images: sex differences - Brown, Rachael; Macefield, Vaughan G. (Frontiers in Physiology, 2014)
While it is known that anxiety or emotional arousal affects skin sympathetic nerve activity (SSNA), the galvanic skin response (GSR) is the most widely used parameter to infer increases in SSNA during stress or emotional studies. We recently showed that SSNA provides a more sensitive measure of emotional state than effector-organ responses. The aim of the present study was to assess whether there are gender differences in the responses of SSNA and other physiological parameters such as blood pressure, heart rate, skin blood flow and sweat release, while subjects viewed neutral or emotionally-charged images from the International Affective Picture System. Changes in SSNA were assessed using microneurography in twenty subjects (ten male and ten female). Blocks of positively-charged (erotica) or negatively-charge images (mutilation) were presented in a quasi-random fashion, following a block of neutral images, with each block containing fifteen images and lasting two minutes. Images of both erotica and mutilation caused significant increases in SSNA, with increases being greater for males viewing erotica and greater for females viewing mutilation. The increases in SSNA were often coupled with sweat release and cutaneous vasoconstriction; however, these markers were not significantly different than those produced by viewing neutral images and were not always consistent with the SSNA increases. We conclude that SSNA increases with both positively-charged and negatively-charged emotional images, yet sex differences are present.